The structure of the singular set of a free boundary in potential theory - L. A. Caffarelli; H. Shahgholian (Հայաստանի ԳԱԱ)
In this paper we characterize the structure of the singular set in the following free boundary problem, where f is Lipschitz.
Keywords: Science; Mathematics